Serum concentrations of vitamin B12 and folate in British male omnivores, vegetarians and vegans: results from a cross-sectional analysis of the EPIC-Oxford cohort study - Gilsing, A; Crowe, F; Lloyd-Wright, Z; Sanders, T; Appleby, P; Allen, N; Key, T (Macmillan Publishers, 2010)
Background/Objectives: Vegans, and to a lesser extent vegetarians, have low average circulating concentrations of vitamin B12; however, the relation between factors such as age or time on these diets and vitamin B12 concentrations is not clear. The objectives of this study were to investigate differences in serum vitamin B12 and folate concentrations between omnivores, vegetarians and vegans and to ascertain whether vitamin B12 concentrations differed by age and time on the diet. Subjects/Methods: A cross-sectional analysis involving 689 men (226 omnivores, 231 vegetarians and 232 vegans) from the European Prospective Investigation into Cancer and Nutrition Oxford cohort. Results: Mean serum vitamin B12 was highest among omnivores (281, 95% CI: 270-292 pmol/l), intermediate among vegetarians (182, 95% CI: 175-189 pmol/l) and lowest among vegans (122, 95% CI: 117-127 pmol/l). In all, 52% of vegans, 7% of vegetarians and one omnivore were classified as vitamin B12 deficient (defined as serum vitamin B12 < 118 pmol/l). There was no significant association between age or duration of adherence to a vegetarian or a vegan diet and serum vitamin B12. In contrast, folate concentrations were highest among vegans, intermediate among vegetarians and lowest among omnivores, but only two men (both omnivores) were categorized as folate deficient (defined as serum folate < 6.3nmol/l). Conclusion: Vegans have lower vitamin B12 concentrations, but higher folate concentrations, than vegetarians and omnivores. Half of the vegans were categorized as vitamin B12 deficient and would be expected to have a higher risk of developing clinical symptoms related to vitamin B12 deficiency.